MiR-200c regulates tumor growth and chemosensitivity to cisplatin in osteosarcoma by targeting AKT2. Issue 1 (December 2017) - Liu, Yang; Zhu, Shu-Tao; Wang, Xiao; Deng, Jun; Li, Wei-Hua; Zhang, Peng; Liu, Bing-Shan
Abstract MicroRNAs (miRNAs) expression aberration has been discovered in almost all human cancers, thus offering a group of potential diagnostic markers, prognostic factors and therapeutic targets in tumorigenesis. Now our data showed that miR-200c, which is downregulated in osteosarcoma tissues, drives chemosensitivity to cisplatin in osteosarcoma. We demonstrated that AKT2 is a direct target of miR-200c, Spearman's rank correlation analysis showed that the expression levels of AKT2 and miR-200c in 35 pairs of osteosarcoma specimens were inversely correlated. Moreover, miR-200c inhibited cell proliferation and cell migration. Taken together, for the first time, our results demonstrate that miR-200c plays a significant role in osteosarcoma tumor growth and chemosensitivity by regulating AKT2, which may provide a novel therapeutic strategy for treatment of osteosarcoma.